St. Patrick's Day in the morning - Bunting, Eve, 1928-; Brett, Jan, 1949- (New York : Clarion, 1980)
Jamie seeks a way to prove he is not too young to march in the big St. Patrick's Day parade.
Elem. School Library Collection.
School Library Journal.
School Library Media Quarterly (A.A.A.L.).
Booklist, February 1998.
Elem. School Library Collection, June 2000.
School Library Journal, June 2011.
Keywords: Parades -- Juvenile fiction; Saint Patrick's Day -- Juvenile fiction; Parades -- Fiction; Saint Patrick's Day -- Fiction; Parades -- Fiction; Saint Patrick's Day -- Fiction; Picture books for children